Ecological characteristics of the area and evaluation of bio indicator species condition in Altyn-Emel State National Natural Park - Cherednichenko, O.G.; Mit, N.V.; Magda, I.N.; Pilyugina, A.L.; Bekmanov, B.O.; Mamilov, N. Sh.; Chirikova, M.A.; Nigai, N.L. (Fundamental and Experimental Biology, 2022)
To assess the degree of contamination and to preserve the natural state of the Altyn-Emel State National Park (Kazakhstan), the monitoring studies were conducted. The total amount of persistent organic pollutants and heavy metals in water and soil samples was determined. Radiodosimetric research, ecological and genetic monitoring of indicator groups of animals were carried out. Chemical analysis revealed the presence of some pollutants exceeding the maximum permissible concentrations in water and soil samples. No area radioactive contamination was detected within the boundaries of the park zone, and the EDR values in general do not ex-ceed the normative values. The exception is the local area of the “Suluchekinskoye” uranium deposit, for which EDR values above the normative values were determined. A comparative analysis of indicator animals showed that their cytogenetic homeostasis, morpho-functional indicators, habitus, and ecological characteris-tics are matched to the normal indexes of animals living in Kazakhstan. Thu s, monitoring studies show that the ecological situation in the “Altyn-Emel” National Park is satisfactory, with some tense circumstances that require constant monitoring.